EMITVEL (Earthquake Mitigation Visual Novel): Media For Learning Earthquake Mitigation in Elementary Schools - Abdillah, Fais Ahnaf; Juhadi, Juhadi; Darmawanti, Ira (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
The study aimed to determine the process of developing EMITVEL application media as a medium for earthquake disaster mitigation in elementary schools and the effectiveness of EMITVEL media as a learning medium for earthquake disaster mitigation. This study uses questionnaires and documentation data collection techniques to adapt the research and development (R/D) phase 1 approach with EMITVEL media development variables. This study concludes by analyzing quantitative descriptions; the EMITVEL application, from the assessment of media experts, is reasonably practical as a learning medium for earthquake disaster mitigation, with details of software engineering aspects at 65%, learning design aspects at 61%, and visual communication aspects 64%. Meanwhile, the practitioner's assessment has effective criteria as a learning medium for earthquake disaster mitigation, with details of 69% software engineering, 66% learning design, and 69% visual communication. This means that the EMITVEL media is suitable as a learning medium for earthquake disaster mitigation in elementary schools.